Replacement broken tiles / Muhammad Idham Noor Effendi - Noor Effendi, Muhammad Idham (Universiti Teknologi MARA, Perak, 2022)
The practical report titled “Replacement the Broken Tiles” covers the complete operation of IIA Construction. The aim of this report is about all the defects that have been found in the house about the broken tiles and submit them to the contractor to make repair work. The main objective is to identify how to replace the broken tiles and collect more detail of all the defects that have been found in the house. On the site, all the defects have been recorded. To conclude, it is important to do change the broken tiles for the reason of safety and customer feel satisfied to live in his house.